2014
DOI: 10.1016/j.chom.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis-Induced Alterations in the Host Cell Proteome Are Required for Intracellular Growth

Abstract: Summary Intracellular pathogens directly alter host cells in order to replicate and survive. While infection-induced changes in host transcription can be readily assessed, post-transcriptional alterations are more difficult to catalog. We applied the global protein stability (GPS) platform, which assesses protein stability based on relative changes in an adjoining fluorescent tag, to identify changes in the host proteome following infection with the obligate intracellular bacteria Chlamydia trachomatis. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…Similar to our findings here (Fig. 3C), the levels of other proteins were diminished without appreciable alterations to the transcript levels (60). Future work will be needed to determine whether C. trachomatis reduces particular host proteins either because they are detrimental to the bacteria or simply because they provide self-peptides for antigen presentation, as demonstrated here.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar to our findings here (Fig. 3C), the levels of other proteins were diminished without appreciable alterations to the transcript levels (60). Future work will be needed to determine whether C. trachomatis reduces particular host proteins either because they are detrimental to the bacteria or simply because they provide self-peptides for antigen presentation, as demonstrated here.…”
Section: Discussionsupporting
confidence: 75%
“…Many times, this manifests itself in alterations to the transcriptome, which have been observed for a variety of Chlamydia species (57)(58)(59). However, a recent report demonstrated that C. trachomatis infection can alter the abundance of host proteins without altering levels of transcripts (60). In this way the bacterium was able to stabilize host components necessary for its survival.…”
Section: Discussionmentioning
confidence: 96%
“…Knockdown of the c-Jun protein altered C. pneumoniae infection, resulting in (i) 20% smaller inclusions, (ii) downregulation of MOMP, (iii) reduction of the chlamydial load, and (iv) a significant decrease in chlamydial recovery. Our findings indicate that growth conditions are suboptimal in the absence of the c-Jun protein and are in line with those described in the report of Olive et al, who found that c-Jun knockdown results in a significant reduction in the level of IFU production (25). In our study, the knockdown effect on infection was possibly limited, since the siRNA approach resulted in only a partial reduction in the level of the c-Jun protein.…”
Section: Discussionsupporting
confidence: 81%
“…In concordance with those findings, we demonstrated that proteins of the AP-1 family are regulated upon chlamydia infection. We found that C. pneumoniae regulates AP-1 proteins mainly at late time points during development, a finding in line with that from a recent study focusing on Chlamydia trachomatis (25). It was demonstrated that the phosphorylation of c-Jun and c-Fos with subsequent AP-1-dependent transcription is induced at a late developmental stage, suggesting that AP-1 is involved in replication or during the redifferentiation process.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation